Feasible Mechanism of Osmotic and Temperature Sensitivity Correction of Human Erythrocytes Using Alkyl-β,D-Glucopyranosides - Shpakova, N. M. (Problems of Cryobiology and Cryomedicine, 2009)
There was studied the effect of glucopyranoside non-ionic derivatives with the alkyl chain length of 6, 8, 10 carbon atoms on hyperosmotic lysis and cold stress development in human erythrocytes. High antihemolytic activity of substances (90–94%) was demonstrated. Efficient concentrations of alkyl glucopyranosides reduce with an increase in alkyl chain length of their molecules. Under cell protection at different lysis types there were calculated the values of ratio of lipid molecule number per 1 molecule of alkyl glucopyranoside in erythrocyte membrane and the membrane concentrations of these substances were established as not significantly differed.